ANALISIS KEBOCORAN & KEBAKARAN TANGKI BLENDING BAHAN BAKAR MIGAS - Sulistiana Agung Riyanto; Vidya Rina Wulandari; Bagas Putra Arfyansyah (Journal of Forensic Expert, 2021)
Explosions and fires that occurred in the blending/mixing tanks of fuel with naphtha to produce pertalite type fuel were initiated by a leak in the tank wall. Based on the results of observations, inspections and tests that have been carried out, the leak of the tank which is the cause of the explosion and fire is the result of the reaction of the tank wall in the weld joint area with base metal (HAZ) which is susceptible to corrosion with acidic tank fluid contents (pH- 5) so as to form an acidic and corrosive environment in the tank with the formation of H2S as a corrosion initiator, reinforced by the discovery of corrosion products in the form of MnS, FeS2, and FeS compounds, elements (S), and the appearance of fractography in the form of white dots indicating uniform corrosion if it occurs for a long time can erode the tank wall and form a leak hole.